Attempts at grapevine (Vitis vinifera L.) breeding through genetic transformation: The main limiting factors - Saporta, R.; San Pedro, Tania; Gisbert, Carmina (Institute for Grapevine Breeding Geilweilerhof, 2021)
Breeding through genetic transformation offers the possibility to add or modify single traits in cultivars without changing desirable characteristics. In grapevine this technology has been scarcely used, taking into account the economic importance of this crop. Up to now, the breeding of grapevine through genetic transformation has been mainly focused on biotic stress resistance, mainly to fungi and viruses. Among the factors that can explain the limited reports of success are the difficulty in regenerating transgenic plants, the availability of only a few characterized genes, and/or the quantitative character of the trait. Another influencing factor is the negative perception of consumers, mainly in Europe. In this review, we discuss the methodology and factors that have limited the success of grapevine transformation, as well as outlining the attempts at breeding grapevine through genetic transformation reported so far. It is expected that the use of transformation, a powerful tool for breeding plants, will increase in grapevine in the coming years as a consequence of the growing knowledge of the function and regulation of grapevine genes and promotors, and of technologies for gene editing.